Opinion on the re‐evaluation of sodium carboxy methyl cellulose (E 466) as a food additive in foods for infants below 16 weeks of age and follow‐up of its re‐evaluation as food additive for uses in foods for all population groups. (9th December 2022) - ; Younes, Maged; Aquilina, Gabriele; Castle, Laurence; Degen, Gisela; Engel, Karl‐Heinz; Fowler, Paul J; Frutos Fernandez, Maria Jose; Fürst, Peter; Gürtler, Rainer; Husøy, Trine; Manco, Melania; et al.
Abstract: Sodium carboxy methyl cellulose (E 466) was re‐evaluated in 2018 by the former EFSA Panel on Food Additives and Nutrient sources added to Food (ANS). As a follow‐up to this assessment, the Panel on Food Additives and Flavourings (FAF) was requested to assess the safety of E 466 for its uses as a food additive in food for infants below 16 weeks of age belonging to food categories (FC) 13.1.5.1 (Dietary foods for infants for special medical purposes and special formulae for infants) in line with Regulation (EC) No 1333/2008. In addition, the FAF Panel was requested to address the issues already identified during the re‐evaluation of the food additive when used in food for the general population, including the safety assessment for FC 13.1.5.1 and 13.1.5.2 (Dietary foods for babies and young children for special medical purposes as defined in directive 1999/21/EC). The process involved the publication of a call for data. Based on the received data, the Panel concluded that the technical data provided by the interested business operator support an amendment of the specifications for sodium carboxy methyl cellulose (E 466) laid down in Commission Regulation (EU) No 231/2012. The interested business operators declared that E 466 is not used in food for infants below 16 weeks of age and in FC 13.1.5.1. Due to the lack of data, an assessment has not been performed for this FC and age group. The interested business operators did not provide biological and toxicological data to support the uses of E 466 in FC 13.1.5.2. Due to the almost unchanged database compared to the situation before the call for data, the FAF Panel confirmed the previous EFSA ANS Panel conclusion according to which the available data did not allow for an adequate assessment of the safety of use of sodium carboxy methyl cellulose (E 466) in infants and young children consuming foods belonging to the FC 13.1.5.2. ©2022 European Food Safety Authority. EFSA Journal published by John Wiley and Sons Ltd on behalf of European Food Safety Authority.